Ex-vivo sensitivity profiling to guide clinical decision making in acute myeloid leukemia: A pilot study. (January 2018) - Swords, Ronan T.; Azzam, Diana; Al-Ali, Hassan; Lohse, Ines; Volmar, Claude-Henry; Watts, Justin M.; Perez, Aymee; Rodriguez, Ana; Vargas, Fernando; Elias, Roy; Vega, Francisco; Zelent, Arthur; et al.
Highlights: Personalized drug treatment recommendations for refractory AML. Ex vivo drug sensitivity screens assessed individual treatment responses. Guided treatments resulted in significantly higher response rates. Abstract: A precision medicine approach is appealing for use in AML due to ease of access to tumor samples and the significant variability in the patients' response to treatment. Attempts to establish a precision medicine platform for AML, however, have been unsuccessful, at least in part due to the use of small compound panels and having relatively slow turn over rates, which restricts the scope of treatment and delays its onset. For this pilot study, we evaluated a cohort of 12 patients with refractory AML using an ex vivo drug sensitivity testing (DST) platform. Purified AML blasts were screened with a panel of 215 FDA-approved compounds and treatment response was evaluated after 72 h of exposure. Drug sensitivity scoring was reported to the treating physician, and patients were then treated with either DST- or non-DST guided therapy. We observed survival benefit of DST-guided therapy as compared to the survival of patients treated according to physician recommendation. Three out of four DST-treated patients displayed treatment response, while all of the non-DST-guided patients progressed during treatment. DST rapidly and effectively provides personalized treatment recommendations for patients with refractory AML.